Evaluation of Knowledge Regarding Cardiopulmonary Resuscitation among Health Care Workers in a Tertiary Care Center of Western Nepal - KC, Sonika; Dhital, Puja Sharma; K.C, Rupak; Bist, Aayush; Belbase, Geeta; Khatri, Binita; Poudel, Ambika Dhakal (Annapurna Journal of Health Sciences, 2025)
Introduction: Cardiopulmonary resuscitation is an essential life-saving procedure for a patient treated in emergencies. Nurses and paramedics are the first responders at the bedside of patients, hence adequate knowledge and skills are highly expected in this profession. This study was carried out to determine the level of knowledge regarding Cardiopulmonary Resuscitation among the health care workers working at Rapti Academy of Health Science, Dang, Nepal.Method: This is a descriptive cross-sectional study design conducted among 148 health workers at Rapti Academy of Health Science, Dang, Nepal. Semi-structured self-administered questionnaire was used to assess the knowledge regarding cardiopulmonary resuscitation. The socio-demographic information and knowledge regarding cardiopulmonary resuscitation among healthcare workers was obtained. Descriptive statistics were presented in tables. The chi-square test was used to explore any possible association between various demographic variables and the level of knowledge in the respondents. Results: Total 64.9% (n=79) of the respondents had an excellent level of knowledge about cardiopulmonary resuscitation. The mean knowledge score of the participants was 31.24 ± 3.08. There is significant association between their level of knowledge with work experience (p=0.02) and previous training (p=0.04) of the participants.Conclusion: The study concluded that, still 35.1% of respondents had moderate level of knowledge about cardiopulmonary resuscitation. Therefore, need of further training and periodic workshop on cardiopulmonary resuscitation is required to help health workers improve upon quality of care while providing cardiopulmonary resuscitation.